Restoration of High Frequency Auditory Perception After Robot-Assisted or Manual Cochlear Implantation in Profoundly Deaf Adults Improves Speech Recognition - Torres, Renato; Daoudi, Hannah; Lahlou, Ghizlene; Sterkers, Olivier; Ferrary, Evelyne; Mosnier, Isabelle; Nguyen, Yann (Frontiers in Surgery, 2021)
Background and purpose: Robot-assisted cochlear implantation has recently been implemented in clinical practice; however, its effect on hearing outcomes is unknown. The aim of this study was to evaluate hearing performance 1 year post-implantation whether the electrode array was inserted manually or assisted by a robot. Methods: Forty-two profoundly deaf adults were implanted either manually (n=21) or assisted by a robot (RobOtol®, Collin, Bagneux, France) with three different electrode array types. Participants were paired by age, and electrode array type. The scalar position of the electrode array in the cochlea was assessed by 3D reconstruction from the pre- and post-implantation computed tomography. Pure-tone audiometry and speech perception in silence (percentage of disyllabic words at 60 dB) were tested on the implanted ear 1 year post-implantation in free-field conditions. The pure-tone average was calculated at 250-500-750 Hz, 500-1000-2000-3000 Hz, and 3000-4000-8000 Hz for low, mid, and high frequencies, respectively. Results: One year after cochlear implantation, restoration of the high-frequency thresholds was associated with better speech perception in silence, but not with low or mid frequencies (p<0.0001; Adjusted R2 = 0.64, polynomial non-linear regression). Although array translocation was similar using either technique, the number of translocated electrodes was lower when the electrode arrays had been inserted with the assistance of the robot compared with manual insertion (p=0.018; Fisher’s exact test). Conclusion: The restoration of high-frequency thresholds (3000-4000-8000 Hz) by cochlear implantation was associated with good speech perception in silence. The numbers of translocated electrodes were reduced after a robot-assisted insertion.